Evaluation of the biocompatibility and antimicrobial properties of biodegradable vascular grafts of various polymer composition with atrombogenic and antimicrobial drug coating - L. V. Antonova; E. O. Krivkina; V. N. Silnikov; O. V. Gruzdeva; M. A. Rezvova; T. N. Akentieva; T. V. Glushkova; V. O. Tkachenko; V. M. Sakharova; L. S. Barbarash (Вестник трансплантологии и искусственных органов)
Creation of vascular grafts with atrombogenic and antimicrobial coating is a very important area.Objective: to evaluate the biocompatibility and antimicrobial properties of biodegradable vascular grafts of various polymer compositions with atrombogenic and antimicrobial drug coating.Materials and methods. Modification of the surface of the biodegradable vascular grafts was performed through complexation with polyvinylpyrrolidone, which was polymerized with polymer scaffold surface by means of ionizing radiation at 10 and 15 kGy. Physical and mechanical properties, as well as hemocompatibility were evaluated. Bacteriological studies were carried out using test strains of gram-negative and gram-positive microorganisms: Klebsiella pneumoniae spp. ozaena No. 5055, Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Proteus mirabillis ATCC3177, Pseudomonas aeruginosa.Results. There was no influence of modifying manipulations with ionizing radiation on the physical and mechanical characteristics of biodegradable prostheses. Vascular grafts with atrombogenic and antimicrobial coatings exhibited atrombogenic properties upon contact with blood, reducing platelet aggregation by 5–7 times (p < 0.05). Also decrease in adhesion and platelets deformation index was found on the surface of drug-eluting scaffolds (for PCL-based prostheses, the latter decreased by 1.9 times relative to unmodified counterparts (p < 0.05), for PHBV/PCL-based prostheses – by 1.3 times relative to unmodified counterparts and 1.5 times relative to scaffolds with polyvinylpyrrolidone (p < 0.05). Bacteriological studies revealed a local inhibitory effect in the place where scaffolds with cationic amphiphile were applied on agar. No growth retardation zones were identified. Polymeric composition of the scaffolds and the used dose of ionizing radiation did not lead to a difference in the bacteriostatic properties of the scaffolds with amphiphile.Conclusion. A full cycle of surface modification of biodegradable polymer prostheses based on both PCL and РHBV/PCL composition resulted in significant increase in the atrombogenic and antimicrobial properties of prostheses and did not worsen the physical-mechanical and biocompatible properties of the structures being developed.